1997
DOI: 10.2307/1244429
|View full text |Cite
|
Sign up to set email alerts
|

Farm Income Variability and the Supply of Off‐Farm Labor

Abstract: If farmers are risk averse, greater farm income variability should increase off-farm labor supply. This effect is confirmed for a sample of Kansas farmers. Off-farm employment of farmers and their spouses is also found to be significantly influenced by farm experience, off-farm work experience, farm size, leverage, efficiency, and farm-specific education. In addition, farm operators and spouses who receive significant income support through government farm programs are less likely to work off the farm. This ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
177
4
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(208 citation statements)
references
References 7 publications
22
177
4
5
Order By: Relevance
“…Moscardi and De Janvry (1977), in their study of attitudes toward risk among peasants in Mexico, found that the higher the off-farm income the higher the capacity to assume risk in agricultural production. Mishra and Goodwin (1997) reported a positive correlation between off-farm employment and farm income variability, indicating that off-farm investment helps many farm households to diversify their income risks. Farm enterprise diversification (DIVERS) has a negative, statistically significant coefficient estimate indicating that diversified dairy farmers are less likely to purchase livestock insurance.…”
Section: Logit Model Resultsmentioning
confidence: 99%
“…Moscardi and De Janvry (1977), in their study of attitudes toward risk among peasants in Mexico, found that the higher the off-farm income the higher the capacity to assume risk in agricultural production. Mishra and Goodwin (1997) reported a positive correlation between off-farm employment and farm income variability, indicating that off-farm investment helps many farm households to diversify their income risks. Farm enterprise diversification (DIVERS) has a negative, statistically significant coefficient estimate indicating that diversified dairy farmers are less likely to purchase livestock insurance.…”
Section: Logit Model Resultsmentioning
confidence: 99%
“…However, in the context of dramatically decreasing incidences of extreme poverty, many Chinese peasants are being left behind and the achievements of development are not being shared [2,3]. In 2016, the per capita disposable income of rural residents was only 36.8% of that of urban residents [4,5]. Under the current market environment, individuals are increasingly paid in accordance with their abilities [6].…”
Section: Introductionmentioning
confidence: 99%
“…First, the paper does not take into account elements of imperfect information and the farm household's attitudes toward risk under uncertainty. It is likely that the production and consumption decisions become non-separable (Mishra and Goodwin, 1997;Benjamin and Kimhi, 2006 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented that income from off-farm activities constitutes an increasingly important part of total household income for farmers. 4 For agricultural households in the United States, for example, it has been shown that there is a positive correlation between farm income variability and off-farm employment, and that off-farm labor earnings play a prominent role for income diversification (Mishra and Goodwin, 1997).…”
Section: Introductionmentioning
confidence: 99%